Influencer Criminalization For Content Harming The Public: A Study Of Criminal Liability In The Digital World - Adam, Sherly; Dj, Akhdiari Harpa; Hamdani, Hamdani (Ipso Jure, 2025)
: In today's digital era, influencers play an important role in shaping public opinion and public behavior through social media. As micro-celebrities, influencers have a strong emotional connection with their followers, which makes them a more trusted source of information than official institutions. However, this large influence poses the risk of disseminating inaccurate information, and even potentially harming the public. This phenomenon is even more complex when influencers spread misinformation or disinformation that has physical, psychological, or social impacts. Although the ITE Act has regulated the dissemination of digital content, it has not explicitly addressed the legal liability of influencers who disseminate harmful content. This creates a legal loophole that influencers can exploit to spread sensational content without considering the negative impacts. This study uses a normative juridical approach to examine the extent to which the ITE Law can accommodate criminal liability for influencers, as well as recommend legal reforms that are more responsive to digital dynamics. This research aims to provide a fairer and more contextual legal construction to overcome challenges in law enforcement in the digital world, while maintaining a balance between freedom of expression and public protection.